2019
DOI: 10.5021/ad.2019.31.1.101
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Cervical Chondrocutaneous Branchial Remnant Comprised of Hyaline Cartilage

Abstract: Cervical chondrocutaneous branchial remnants (CCBRs) are rare, congenital, benign neck masses, and are derived from dislocated branchial apparatus components com

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Therefore, CCBRs are likely best considered a second branchial remnant disorder, and the use of particular terms such as cervical auricle and accessory tragus should be avoided. 10…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, CCBRs are likely best considered a second branchial remnant disorder, and the use of particular terms such as cervical auricle and accessory tragus should be avoided. 10…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CCBRs are likely best considered a second branchial remnant disorder, and the use of particular terms such as cervical auricle and accessory tragus should be avoided. 10 Recent studies have further expanded upon the various histologic features of CCBRs, with large nerves and clusters of Pacinian corpuscles documented at the periphery of these lesions. It has been hypothesized that the chondrocutaneous remnants attract sensory axons and neural crest cells that organize as Pacinian corpuscles in the vicinity of cartilage, as has been described in other cartilage or connective tissues.…”
Section: Discussionmentioning
confidence: 99%
“…These sonographic findings are useful for differentiating dermal cervical lesions. To date, case reports and other studies of CCBRs have been published mainly by otolaryngologists, dermatologists, pediatric surgeons, and plastic surgeons; [8][9][10][11][12]25,26,[29][30][31][32] sonographers and radiologists were not familiar with this disease. In the current study, we identified diagnostic characteristics that suggest the presence of a CCBR in ultrasound examinations.…”
Section: Discussionmentioning
confidence: 99%
“…appendages. 1,[3][4][5] CCBRs are usually located at the lower neck on the anterior or posterior border of the sternocleidomastoid muscle (SCM), 3,[6][7][8][9][10][11][12] which is also the site of other dermal lesions such as epidermoid cysts or branchial anomalies including lateral cervical cysts/sinuses or dermal sinuses of anterior chest lesions. [13][14][15][16][17] The clinical presentation of CCBRs varies and includes skin tag lesions or lesions with fistula connections to deeper structures.…”
mentioning
confidence: 99%
See 1 more Smart Citation